1996
DOI: 10.1068/p250983
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Salience of Haptic Object Properties: Role of Modality-Encoding Bias

Abstract: The influence of modality-encoding bias on the relative importance ('cognitive salience') of object shape, size, and material, with the last determined by weight and thermal variations, was examined. Experiment 1 confirmed that for these stimulus objects all five properties were very accessible haptically, as measured by the time to identify the property level of each designated property; however, observers were still generally faster for geometric than material properties. In experiment 2, the influence of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 20 publications
4
26
0
Order By: Relevance
“…When the properties of objects are matched for perceptual discriminability, observers judging interobject similarity attend to material properties (texture, compliance, thermal, and weight) more when objects are encoded by touch alone than when objects are seen while being touched. Conversely, they weight geometric properties (2-D and 3-D shape and size) more when examining the same objects with vision present than by touch alone (e.g., Klatzky, Lederman, & Reed, 1987;Lederman, Summers, & Klatzky, 1996). The greater salience of material properties under haptic exploration presumably reflects the findings that a greater number of EPs convey information about material than geometry, and that EPs optimized for encoding material (cf.…”
Section: Haptic Perception Of Multiattribute Objectsmentioning
confidence: 90%
“…When the properties of objects are matched for perceptual discriminability, observers judging interobject similarity attend to material properties (texture, compliance, thermal, and weight) more when objects are encoded by touch alone than when objects are seen while being touched. Conversely, they weight geometric properties (2-D and 3-D shape and size) more when examining the same objects with vision present than by touch alone (e.g., Klatzky, Lederman, & Reed, 1987;Lederman, Summers, & Klatzky, 1996). The greater salience of material properties under haptic exploration presumably reflects the findings that a greater number of EPs convey information about material than geometry, and that EPs optimized for encoding material (cf.…”
Section: Haptic Perception Of Multiattribute Objectsmentioning
confidence: 90%
“…They found that although haptics and vision use broadly similar perceptual maps for comparing stimuli, shape was much more important than texture for vision, whereas shape and texture were similarly important for haptics. In a free-sorting task, Lederman, Summers, and Klatzky (1996) found that shape was the most salient dimension for both touch and vision, and that shape was more salient for vision than for touch. Size was as rapidly available as shape for haptics, but it was not a salient dimension for either touch or vision.…”
Section: Methodsmentioning
confidence: 99%
“…For example, geometric tasks that require haptic recognition without vision are performed relatively poorly, whereas material properties are processed more precisely and quickly. Furthermore, there is dominance of vision over haptics on extracting geometric information because vision can extract spatial details far more precisely and faster than can any haptic exploration procedure (Lederman et al, 1996).…”
Section: Benefits Of Haptics To Understanding Learning and Educationmentioning
confidence: 99%
“…Haptic perception and representation are based on inputs from mechanoreceptors and thermoreceptor subsystems in the skin, as well as on position-sensing and force-sensing mechanisms that exist in muscles, tendons and joints (Lederman et al, 1996). By exploiting the haptic system, subjects are able to extract different kinds of information from the manual exploration of objects (Lederman and Klatzky, 1987) such as their material properties (e.g., surface texture, hardness, thermal, weight), their geometric properties (those pertaining to shape and size), their mechanical properties (e.g., motion of an object part), and their functional properties (as determined from object structure).…”
Section: Benefits Of Haptics To Understanding Learning and Educationmentioning
confidence: 99%